Anak Sebagai Pelaku Penyalahguna Narkotika Dikaitkan Dengan Konsep Eksploitasi Dan Kejahatan Terorganisasi - Rida Aristawati (Faculty of Law, Universitas Airlangga, 2022)
Abstract This article was written using normative legal research that uses a conceptual approach and statute approach. In this paper, the focus is on discussing children as narcotics abusers associated with the concept of exploitation and qualifications of organized crime perpetrators. Children who are involved as narcotics abusers can qualify as perpetrators. Moreover, narcotics trafficking is closely related to organized crime so that children can also qualify as perpetrators of organized crime if they are known to be involved in them. In Law No. 35 of 2009 concerning Narcotics there is a criminal weighting, namely 1/3. When children are involved as perpetrators of narcotics abusers, it is very close to exploitation because in Law No. 35 of 2014 concerning Child Protection and Law No. 35 of 2009 concerning Narcotics, several regulations have been formulated regarding the prohibition of exploitation of children, especially in relation to the abuse of narcotics and their production and distribution. So that children who are involved in the crime of narcotics abusers can qualify as perpetrators and victims of exploitation. Keywords: Children; Narcotics Abusers; Exploitation; Organized Crime. Abstrak Artikel ini ditulis dengan menggunakan penelitian hukum normatif yang menggunakan pendekatan konseptual serta pendekatan peraturan perundang-undangan. Dalam penulisan ini difokuskan membahas mengenai anak sebagai pelaku penyalahguna narkotika dikaitkan dengan konsep eksploitasi dan kualifikasi pelaku kejahatan terorganisasi. Anak yang dilibatkan sebagai penyalahguna narkotika maka anak dapat dikualifikasikan sebagai pelaku. Terlebih lagi dalam tindakan pengedaran narkotika sangat berkaitan erat dengan kejahatan terorganisasi sehingga anak juga dapat dikualifikasikan sebagai pelaku kejahatan terorganisasi apabila diketahui terlibat didalamnya. Dalam Undang-Undang No. 35 Tahun 2009 tentang Narkotika terdapat pemberatan pidana yakni 1/3. Ketika anak dilibatkan sebagai pelaku penyalahguna narkotika sangat bersinggungan dengan tindakan eksploitasi sebab dalam Undang-Undang No. 35 Tahun 2014 tentang Perlindungan Anak dan Undang-Undang No. 35 Tahun 2009 tentang Narkotika telah dirumuskan beberapa aturan mengenai larangan tindakan eksploitasi terhadap anak terutama dalam kaitannya dengan penyalahgunaan narkotika beserta produksi dan distribusinya. Sehingga anak yang dilibatkan dalam tindak pidana penyalahguna narkotika dapat dikualifikasikan sebagai pelaku serta korban dari eksploitasi. Kata Kunci: Anak; Penyalahguna Narkotika; Eskploitasi; Kejahatan Terorganisasi.